2017
DOI: 10.3389/fpubh.2017.00185
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Palliative Care Initiative in Cambodia

Abstract: Cancer care with curative intent remains difficult to manage in many resource-limited settings such as Cambodia. Cambodia has a small workforce with limited financial and health-care resources resulting in delayed diagnoses and availability of limited therapeutic tools. Thus, palliative care becomes the primary form of care in most cases. Although palliative care is becoming an integral part of medical care in developed countries, this concept remains poorly understood and utilized in developing countries. Ang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(32 citation statements)
references
References 16 publications
0
26
0
6
Order By: Relevance
“…In our study, we documented these cases to be as high as 6.8%, revealing an important subset of patients who are not receiving curative‐intent oncological treatment due to very advanced disease at onset or poor performance status. Other studies in LMIC have reported variable rates of children receiving palliative‐only care, calling for an interdisciplinary approach for progressive, debilitating, or life‐limiting illnesses such as cancer . In Peru, advanced disease at diagnosis is found in as much as 37% of pediatric cancer cases .…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we documented these cases to be as high as 6.8%, revealing an important subset of patients who are not receiving curative‐intent oncological treatment due to very advanced disease at onset or poor performance status. Other studies in LMIC have reported variable rates of children receiving palliative‐only care, calling for an interdisciplinary approach for progressive, debilitating, or life‐limiting illnesses such as cancer . In Peru, advanced disease at diagnosis is found in as much as 37% of pediatric cancer cases .…”
Section: Discussionmentioning
confidence: 99%
“…21 Similarly, countries in Asia including India, China, Vietnam, and Cambodia, among others, reported a similar ICU capacity ( Figure 3). [22][23][24][25][26][27][28][29] Table 1.…”
Section: Number Of Icu Beds Per 100000 Populationmentioning
confidence: 99%
“…Research findings based on themes: This integrative review was presented under the two major themes which were referred to as: Gaps in PPC standards, practice framework and guidelines: Nine out of 11 studies included in this review highlighted topics related to emerging standards, practice framework and guidelines. [9][10][19][20][21][22][23][24][25] These topics which pertains to the essential domains of a so called standards and practice guidelines refer to 'service models', [9,20,[22][23]25] 'management of symptoms', [10,21,24] 'structural environment', [10,[19][20][23][24][25] and 'regulations'. [23][24] PPC barriers and challenges, and implementation strategies: This theme originated from all 11 studies.…”
Section: Resultsmentioning
confidence: 99%